Corporate philanthropy with Islamic spirit at Hamidah Thoibah Enterprise - Shayuty, Thanaa'; Mhd. Sarif, Suhaimi (Academy of Contemporary Islamic Studies (ACIS), UiTM, 2017)
This study explores the practice of corporate philanthropy with Islamic spirit at Hamidah Thoibah Enterprise. Corporate philanthropy has been understood as corporate social responsibility and making charity while doing business. Such understanding is in line with the stakeholder theory, property theory and welfare economics. From the studies of Business Ethics, philanthropic responsibilities as the highest level of responsibility for corporate entities. In Islamic theological studies, philanthropy is benevolent act, as part of Islamic teachings. Based on the theoretical, policy and practical background, this study argues that corporate philanthropy with Islamic spirit enables business entities such as Hamidah Thoibah Enterprise to sustain its business for long term. This study uses positivism case study method to explore the effect of Islamic spirit of corporate philanthropy at Hamidah Thoibah Enterprise.